2019
DOI: 10.1192/bjo.2018.84
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive simvastatin for treatment-resistant depression: study protocol of a 12-week randomised controlled trial

Abstract: BackgroundA third of patients diagnosed with major depressive disorder (MDD) experience treatment-resistant depression (TRD). Relatively few pharmacological agents have established efficacy for TRD. Therefore, the evaluation of novel treatments for TRD is a pressing priority. Statins are pleiotropic agents and preclinical studies as well as preliminary clinical trials have suggested that these drugs may have antidepressant properties.AimsTo report on a protocol for a 12-week, randomised, double-blind, placebo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Likewise, evidence from most observational studies in non-depressed populations reported that simvastatin had the most beneficial effects (87,90), though another study reported a conflicting finding (76). Again, data from the previously mentioned ongoing trials (146,147), which are both using the highly lipophilic simvastatin, possibly corroborated by further observational studies comparing the effects of individual lipophilic and hydrophilic statins, could provide further useful evidence.…”
Section: Discussionmentioning
confidence: 87%
“…Likewise, evidence from most observational studies in non-depressed populations reported that simvastatin had the most beneficial effects (87,90), though another study reported a conflicting finding (76). Again, data from the previously mentioned ongoing trials (146,147), which are both using the highly lipophilic simvastatin, possibly corroborated by further observational studies comparing the effects of individual lipophilic and hydrophilic statins, could provide further useful evidence.…”
Section: Discussionmentioning
confidence: 87%
“…Because there is evidence for central inflammation in depressed patients [ 49 ], it is possible that drugs able to modulate brain inflammatory mechanisms directly may be more therapeutically active. Further clinical trials of statins in depressed patients should therefore consider the specific statins profile when selecting the molecule to be used: a currently running randomised controlled trial chose indeed to use simvastatin in addition to antidepressant [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings could have implications for antiinflammatory treatment 6,65 and preventative care [66][67][68][69] in a subgroup of depressed patients with sickness-behaviorrelated symptoms 70 . Research is underway to investigate the effects of anti-TNF-alpha biologic infliximab on measures of anhedonia, motivational behavior, and glutamatergic changes in the basal ganglia 71 and to investigate the effects of simvastatin for treatment-resistant MDD 72 and patients with comorbid obesity and MMD 73 . We recommend that future studies approach depression as a group of separate symptoms rather than as a unified construct.…”
Section: Discussionmentioning
confidence: 99%